The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/sres.2277
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Dynamic Relationship between Higher Educational Investment and Economic Growth using VAR Model

Abstract: Previous research has studied the relationship between higher education and economic growth, but the results are mixed. This paper analysed higher educational investment and economic growth theoretically and studied the long‐term dynamic relationship between them by using Johansen test, Granger causality test, impulse response function, variance decomposition and other empirical methods based on vector autoregressive model. The result indicates a long‐term stable equilibrium relationship among higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
2
Order By: Relevance
“…The estimated results also suggest a noteworthy and affirmative correlation between LGHEs and economic progress, as the long-term effects were greater than the short-term ones, which reinforces previous research indicating that augmenting investments in local general higher education positively influences economic growth [ 18 , 61 ]. However, our estimates are larger than those of previous studies [ 60 , 62 ]. One explanation is that the results may be underestimated when no spatial effect is considered.…”
Section: Conclusion and Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The estimated results also suggest a noteworthy and affirmative correlation between LGHEs and economic progress, as the long-term effects were greater than the short-term ones, which reinforces previous research indicating that augmenting investments in local general higher education positively influences economic growth [ 18 , 61 ]. However, our estimates are larger than those of previous studies [ 60 , 62 ]. One explanation is that the results may be underestimated when no spatial effect is considered.…”
Section: Conclusion and Discussioncontrasting
confidence: 91%
“…larger than those of previous studies [60,62]. One explanation is that the results may be underestimated when no spatial effect is considered.…”
Section: Plos Onecontrasting
confidence: 63%
“…Lin () found that spending for higher education significantly and positively influenced Taiwan's economic growth both in terms of industrial and agricultural output. In a study of China, Yu et al () Granger analysed public expenditures for both higher education and human capital development vis‐à‐vis economic growth and found a long‐term stable equilibrium relationship between them, specifically one in which both the expenditures and human capital investment had a significant positive Granger‐causal impact on economic growth. Also in China, Huang et al’s () Granger tests of enrolments in higher education and economic growth from 1972–2007 found bidirectional causality and led them to conclude that while expansion of higher education will promote growth up to a point, it should not be invested in blindly because thereinafter it may lead to decreases in the efficiency of resource investment, diminishing marginal utility and eventually to negative value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This special issue of Systems Research and Behavioral Science presents 11 articles reflecting the above‐mentioned three elements (Jin et al , ; Tan et al , ; Jiang et al , ; Pan et al , ; Wang et al , ; Yu et al , ; Qi et al , ; Li et al , ; Shan et al , , ; Yu et al , ). These papers show the evidence that it is desirable to apply systems approach or methodologies to many different fields (Yu et al , ; Wan and Jones, ; Zhao et al , ).…”
Section: Introduction: Systems Science Methods In Industrial Sectormentioning
confidence: 99%